Short term load forecasting for a micro region using NNs and regression models - Kaysal, Kubra; Hocaoglu, Fatih Onur; Oguz, Yuksel; Kaysal, Ahmet (ELECO : 2013 8th International Conference on Electrical and Electronics Engineering : 28-30 November 2013, 2013)
Thanks to today's advancing technology, some techniques have been developed to make future oriented forecast on energy generation, transmission and distribution subjects. In literature, load forecasting studies are generally realized for macro size settlement units. However, determination of parameters that effect load forecasting in macro size settlement units is very difficult. In this study, by considering a micro size settlement unit (Güney district of Denizli province), factors that may affect the load demand were examined. Then, by selecting popular methods used in the literature, load forecasting for the region was realized. Finally the results obtained from the models were compared.